Perbuatan Melawan Hukum Menguasai Tanah Hak Milik Orang Lain (Studi Putusan Mahkamah Agung Nomor 3302 K/Pdt/2018) - M. Faisal Rahendra Lubis (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
Unlawful deed are an adverse effect to the rights of other people created by the law. This indicates that unlawful deed of disobedience based on consent and legal actions resulting from man’s own actions. Studies suggest that an act is unlawful when it adds to the several elements of an act, it must unlawful deed, it must inflict harm, it is wrong, and between the act and the harm inflicted there must be a causal relationship. Unlawful deed in this case by violating the ordinance in article 1335 dan article 1337 KUHPerdata, that is a forbidden cause and the existence of covenant matters or materials in violation of the law make it subject to article 1365 KUHPerdata. It was concluded that elements of unlawful deed constituted unlawful deed performed by the individual and those works were contrary to the right of another person to possession of property that didn’t belong to him. As a result when a man takes possession of the land of another’s property, the owner of the land of another’s property is required to vacate and return the land of property rights to its owner. All forms of deeds are categorized unlawful deed when they are unlawful deed, and when an individual has done wrong at the expense of the rights of another.Keywords: Unlawful Deeds, Legal Consequences, Land Of Proferty